COMPARISON ON THE PERFORMANCE OF PREFABRICATED VERTICAL DRAIN (PVD) PRELOADING COMBINED WITH AND WITHOUT VACUUM AND HEAT - J. Saowapakpiboon; D. T. Bergado; S. Artidteang (International Association of Lowland Technology, 2011)
This paper focus on performance of prefabricated vertical drain (PVD) preloading combined with and without vacuum and heat to accelerate the consolidation of soft Bangkok clay. The laboratory tests were conducted using reconstituted specimens in large scale consolidometers combined with and without vacuum and heat. The flow parameters were back calculated in terms of the horizontal coefficient of consolidation (Ch) and the ratio between the horizontal permeability in undisturbed zone (kh) to the horizontal permeability in smear zone (ks) or (kh/ks) based on Hansbo (1979) method. The back-calculation analysis results show that the combination of vacuum pressure and heat can increase the horizontal coefficient of consolidation, Ch of 126.42% and decrease of kh/ks of 63.33%. Furthermore, vacuum can increase higher rate of consolidation temperature can decrease viscosity of pore water by reducing the drainage retardation effects in the smear zone around the PVD which resulted in faster rate of consolidation and higher magnitude of settlement.